Comparative analysis of tools for managing web application development - Paulina Wójcik; Małgorzata Plechawska-Wójcik (Journal of Computer Sciences Institute)
This article presents a comparative analysis of three bundlers: tools for managing web application development. The basic capabilities of the Webpack, Parcel and Vite tools were reviewed. Bundlers were examined in terms of performance, as well as ease of configuration. The article describes the configuration of each of the tools studied. Research scenarios were formulated, on the basis of which a series of tests were carried out consisting in building applications by each tool and measuring the parameters of this process. The obtained results of the research and the author's personal experience made it possible to choose the best tool for managing web application development.